Maternal Caffeine Intake and Risk of Selected Birth Defects in the National Birth Defects Prevention Study - Browne, Marilyn L. (Birth Defects Res A Clin Mol Teratol, 2011)
BACKGROUND: Caffeine intake is common during pregnancy, yet few epidemiologic studies have examined the association between maternal caffeine consumption and birth defects. Using data from the National Birth Defects Prevention Study (NBDPS), we examined the association between maternal caffeine consumption and anotia/microtia, esophageal atresia, small intestinal atresia, craniosynostosis, diaphragmatic hernia, omphalocele, and gastroschisis. METHODS: The NBDPS is a multi-site population-based case-control study. The present analysis included 3,346 case infants and 6,642 control infants born from October 1997 through December 2005. Maternal telephone interview reports of demographic characteristics and conditions and exposures before and during pregnancy were collected. Odds ratios and 95% confidence intervals, adjusted for relevant covariates, were calculated to estimate the associations between maternal dietary caffeine intake (coffee, tea, soda, and chocolate) and maternal use of caffeine-containing medications and each defect. RESULTS: We observed small, statistically significant elevations in adjusted odds ratios ranging from 1.3 to 1.8 for total maternal dietary caffeine intake or specific types of caffeinated beverages and anotia/microtia, esophageal atresia, small intestinal atresia, and craniosynostosis; however, dose-response patterns were absent. Periconceptional use of caffeine-containing medications was infrequent and estimates were imprecise. CONCLUSIONS: We did not find convincing evidence of an association between maternal caffeine intake and the birth defects included in this study. The increasing popularity of caffeine-containing energy drinks and other caffeinated products may result in higher caffeine intake among women of childbearing age. Future studies should consider more detailed evaluation of such products.